A prospective comparison of totally minimally invasive versus open Ivor Lewis esophagectomy. Issue 3 (23rd May 2012) - Noble, F.; Kelly, J. J.; Bailey, I. S.; Byrne, J. P.; Underwood, T. J.; ,
Summary The majority of esophagectomies in Western parts of the world are performed by a transthoracic approach reflecting the prevalence of adenocarcinoma of the lower esophagus or esophagogastric junction. Minimally invasive esophagectomy (MIE) has been reported in a variety of formats, but there are no series that directly compare totally minimally invasive thoracolaparoscopic 2 stage esophagectomy (MIE‐2) with open Ivor Lewis (IVL). A prospective single‐center cohort study of patients undergoing elective MIE‐2 or IVL between January 2005 and November 2010 was performed. Short‐term clinicopathologic outcomes were recorded using validated systems. One hundred and six patients (median age 66, range 36–85, 88 M : 18 F) underwent two‐stage esophagectomy (53 MIE‐2 and 53 IVL). Patient demographics (age, sex, body mass index, American Society of Anesthesiologists grade, tumor characteristics, neoadjuvant chemotherapy, and TNM stage) were comparable between the two groups. Outcomes for MIE‐2 and IVL were comparable for anastomotic leak rates (5 [9%] vs. 2 [4%], P= 0.241), resection margin clearance (R0) (43 [81%] vs. 38 [72%], P= 0.253), median lymph node yield (19 vs. 18, P= 0.584), and median length of stay (12 [range 7–91] vs. 12 [range 7–101] days), respectively. Blood loss was significantly less for MIE‐2 compared with IVL (median 300 [range 0–1250] mL vs. 400 [range 0–3000] mL, respectively, P= 0.021). MIE‐2 in this series of selected patients supports its efficacy, when performed by an experienced minimally invasive surgical team. A well‐designed multicenter trial addressing clinical effectiveness is now required.